Kepercayaan Terhadap Supervisor Pada Staf Garis Depan: Kualitas Hubungan Sebagai Moderator - Azizah, Siti Nur (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2021)
This study investigates the antecedents of a frontline employee’s trust-in-supervisor with relation quality as moderator variable. This research is a causal descriptive study to investigate the relationship between variables. A personally administered survey was conducted to collect data from 100 frontline employees in Kebumen District, Cenral Java, Indonesia. Covariance-based structural equation modeling was applied using PLS3 to explore the proposed relationships. The results show that abusive supervision is negatively related to frontline employee’s trust-in-supervisor, whereas supervisor support and communication quality have significant positive effects on frontline employee’s trust-in-supervisor. Finally, the results show that relationship quality moderates (strengthens) the supportive influence of supervisors on trust in supervisors, but the quality of the relationship does not moderate the effect of abusive supervisors on trust in supervisor